FIQH AL-HADÃTS: Perspektif Historis dan Metodologis - Saifuddin, Saifuddin (Fakultas Ushuluddin dan Humaniora IAIN Antasari, 2012)
Study of fiqh hadith Sharh Hadith is one of interested topic to discuss. Study of fiqhÂ al-Hadith is a multidisciplinary field of study that involves almost all branches ofÂ hadith disciplines, involving sanad sciences, Rijal al-Hadith sciences, as well as matnÂ sciences. The science is in its infancy still simple, then grow gradually and extends toÂ become an independent branch of science known as Sharh Hadith al-hadith or fiqh.